Comparison of Metformin and Repaglinide Monotherapy in the Treatment of New Onset Type 2 Diabetes Mellitus in China - J. Ma; L. Y. Liu; P. H. Wu; Y. Liao; T. Tao; W. Liu (Journal of Diabetes Research)
Objective. This study was designed to compare the effects of metformin and repaglinide on the fasting plasma glucose (FPG) and glycated haemoglobin (HbA1c) in newly diagnosed type 2 diabetes in China. Methods. A total of 107 newly diagnosed type 2 diabetic patients (46 women and 61 men) participated in the study. All patients received 3-month treatment of metformin or repaglinide. Fasting blood glucose and HbA1c were determined at baseline and at the end of the 3-month of treatment. Results. FPG and HbA1c decreased in both metformin and repaglinide groups after 3 months treatment (P<0.01). The reduction of HbA1c was significantly greater in the repaglinide group (P<0.01). Metformin decreases fasting insulin concentration and HOMA-IR (P<0.01), and repaglinide improves HOMA-β  (P<0.01). Triglycerides (TG) were reduced in both groups (P<0.01 in metformin group; P<0.05 in repaglinide group), but total cholesterol (TC) and low-density lipoprotein (LDL) were decreased only after metformin treatment (P<0.05). Conclusions. Both repaglinide and metformin were effective in glycaemic control in new onset patients with type 2 diabetes in China. Repaglinide had no effect on insulin sensitivity, but it improved β-cell function.